2016
DOI: 10.1248/bpb.b15-00565
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Discrepancies between Pharmacist and Patient Perception of the Pharmacist’s Role as an Advisor on Drug Therapy Based on Social Science Theory

Abstract: Article 25-2 of the Japanese Pharmacists' Act was revised in June 2014, establishing the position of pharmacists as "advisors on the use of pharmaceuticals." Prior to the Act's revision, we investigated the perceptions of patients and pharmacists about pharmacists' roles using a social science methodology. We also examined current opinions and necessary factors for the future growth and development of pharmacists. This questionnaire survey was conducted using an internet method. Patients and pharmacists answer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 13 publications
5
22
0
Order By: Relevance
“…The patient explored the most reason of visiting pharmacy before physician due to the pharmacist help the patient in health diseases and the patients relied that's pharmacies had better knowledge of medications and adverse drug reaction than others health care professionals. The results of medication knowledge of pharmacist better than physician resemble what reported by Khan MU et al [20] and better than what reported by Oshima S et al [7] Maybe the pharmacist role not developed in that country very well. In addition, the pharmacist visited the pharmacy for medical consultation and refuse to consider the pharmacist as cosmetic seller.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The patient explored the most reason of visiting pharmacy before physician due to the pharmacist help the patient in health diseases and the patients relied that's pharmacies had better knowledge of medications and adverse drug reaction than others health care professionals. The results of medication knowledge of pharmacist better than physician resemble what reported by Khan MU et al [20] and better than what reported by Oshima S et al [7] Maybe the pharmacist role not developed in that country very well. In addition, the pharmacist visited the pharmacy for medical consultation and refuse to consider the pharmacist as cosmetic seller.…”
Section: Discussionsupporting
confidence: 62%
“…Several studies investigated the patient perception of pharmacist over all the world. [7][8][9][10] Some studies investigated the general perception of the pharmacist's personal and others discussed the perception of pharmacist duties or pharmacy services at each organization. Some studies showed well and some shoes bad attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we have previously conducted research using the same type of internet research. [15][16][17][18][19] Survey Responses and Data Analysis The work flow from administration of the survey to analysis of the data is shown in Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4] However, to the best of our knowledge, studies investigating the healthcare professionals' perception during pharmacy visit toward a pharmacist are scarce. [5][6] Furthermore, there are no studies conducted in Saudi Arabia, the Gulf and Middle Eastern countries on the aforementioned topic. Therefore, in this study, we aimed to explore healthcare professionals' perception toward a pharmacist during pharmacy visit in the Kingdom of Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%